2017
DOI: 10.3139/146.111526
|View full text |Cite
|
Sign up to set email alerts
|

Current developments of biomedical porous Ti–Mo alloys

Abstract: Current developments of biomedical porous Ti-Mo alloysAs a biomedical hard tissue implant candidate, porous Ti-Mo alloy has received considerable attention because of its special porous structure, appropriate Young's modulus and compressive strength as well as good corrosion resistance. As a bioactive coating, hydroxyapatite is commonly used to cover the surface of bioinert metallic prostheses due to its excellent biocompatibility, bone-like structure and composition. This article reviews the current developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…While blood contact implants with minimal interaction are normally required for implants that remain in contact with blood, osseointegrated implants must have strong interaction in order to obtain a high adhesion force. Osteointegration can be influenced by both the structure and topography of the surface and its composition [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While blood contact implants with minimal interaction are normally required for implants that remain in contact with blood, osseointegrated implants must have strong interaction in order to obtain a high adhesion force. Osteointegration can be influenced by both the structure and topography of the surface and its composition [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium may result in some toxic effects like hematological reactions [1,2]. Recent reports reveal that Mo, Nb, Ta, Zr, and Sn belong to biocompatible alloying elements without or with much lower cytotoxicity [1,2,[4][5][6][7][8]. Accordingly, novel kinds of biomedical near β Ti alloys possessing smaller YM have been studied by selecting the above-mentioned alloying elements.…”
Section: Element Selection Of the New Biocompatible Solid Ti Alloymentioning
confidence: 99%
“…One of the promising alloying elements is Mo, especially for good biocompatibility, corrosion resistance and metallurgical effects, to which is added a low manufacturing cost comparatively with other alloying elements. Increasing the Mo content reduces the transition temperature of the β phase, decreases the elastic modulus and balances the pH in the body [22,23]. Recent research has shown that the use of about 18 wt.% Zr and 13 wt.% Mo as alloying elements for titanium has led to high values for yield stress and good ductility.…”
Section: Introductionmentioning
confidence: 99%